2008
DOI: 10.1186/1475-2840-7-25
|View full text |Cite
|
Sign up to set email alerts
|

Anaemia and kidney dysfunction in Caribbean Type 2 diabetic patients

Abstract: BackgroundAnaemia has been shown in previous studies to be a risk factor for cardiovascular disease in diabetic patients with chronic kidney disorder. This study was aimed to assess the prevalence of anaemia and kidney dysfunction in Caribbean type 2 diabetic patients that have been previously shown to have a high prevalence of the metabolic syndrome.Methods155 type 2 diabetic patients and 51 non-diabetic subjects of African origin were studied. Anthropometric parameters were measured and fasting blood samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
45
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 20 publications
10
45
1
1
Order By: Relevance
“…In contrast, study conducted by Ezenwaka CE et al, out of 155 patients of type 2 diabetes mellitus, 72 (46.45%) were anaemic and 83 (53.54%) were non anaemic. 8 In another study, conducted by Cawood TJ et al, out of 270 patients only 34 (12.29%) were anaemic. 9 The higher prevalence of anaemia in our study was probably due to lack of knowledge about balanced diet, increased incidence and prevalence of infection and chronic diseases, malnutrition due to poverty and poor access to medical care.…”
Section: Prevalence Of Anaemiamentioning
confidence: 92%
See 1 more Smart Citation
“…In contrast, study conducted by Ezenwaka CE et al, out of 155 patients of type 2 diabetes mellitus, 72 (46.45%) were anaemic and 83 (53.54%) were non anaemic. 8 In another study, conducted by Cawood TJ et al, out of 270 patients only 34 (12.29%) were anaemic. 9 The higher prevalence of anaemia in our study was probably due to lack of knowledge about balanced diet, increased incidence and prevalence of infection and chronic diseases, malnutrition due to poverty and poor access to medical care.…”
Section: Prevalence Of Anaemiamentioning
confidence: 92%
“…Another study done by Ezenwaka CE et al, reported that anaemic patients of diabetic group had significantly lower creatinine clearance (67.1±3.0ml/min) than non diabetic (57.9±5.4ml/min) and it was significant (p<0.001). 8 …”
Section: Creatinine Clearancementioning
confidence: 99%
“…This prevalence is comparable to that reported in diabetic patients in Australia, 5 but was much lower than that reported in the US (34.7%) 15 and in Caribbeans (46.5%). 4 The disparity could be partially explained by different degrees of diabetes severity managed in primary and secondary care in these regions. Diabetic patients with stable metabolic control and less severe complications are more likely to be managed in the primary care and therefore have a lower prevalence of anaemia compared with those managed in secondary or tertiary settings.…”
Section: Discussionmentioning
confidence: 99%
“…4 The greatest decrease in haemoglobin (Hb) levels was noted in patients with macroalbuminuria and renal impairment. Indeed, anaemia is a well-known complication of chronic kidney disease (CKD) and is now recognised as an early component of diabetic nephropathy.…”
Section: Introductionmentioning
confidence: 99%
“…The blood serves many key roles such as nutritional, homeostatic and immunologic processes (Oze, 1992), tissue and pulmonary respiration, endocrine processes, and excretion of metabolic wastes (Adebayo et al 2005). Ezenwaka et al (2008) reported a high prevalence of anemia in patients with Type 2 diabetes, as much as 27% (Dipta et al 2009). In addition, diabetes induces and promotes hematological disorders, where the occurrence of anemia in a hyperglycemic patient results from non enzymatic glycosylation or stiffening of the membrane proteins of the Red Blood Cells (Kennedy and Baynes, 1984).…”
Section: Introductionmentioning
confidence: 99%